(untitled) (Research, Society and Development, 2020)
The use of chemical fertilizers increases the costs of species production systems fruit trees like the fig tree, making it necessary to look for fertilizers of organic origin and whichare of low cost, presenting nutrients readily available, to evaluate the agronomic performance of fig tree cv. ’Roxo de Valinhos’, submitted to different organic fertilizers. The experiment was conducted at the Federal Institute of Paraíba, Campus Sousa. The experimental design used was randomized blocks, with five treatments corresponding to different sources of organic fertilizers (F1: without fertilization (Witness); F2: poultry litter; F3: sheep manure; F4: cattle manure and F5: compost organic) and four replications, with the experimental unit consisting of three plants. The seedling production was carried out by the cutting method, with branches of the cultivar ’Roxo de Valinhos’. The variables analyzed were plant height, diameter of the crown, number of branches, number of leaves and fruits, fruit weight, fruit diameter(longitudinal and transversal), longitudinal and transversal diameter ratio, soluble solids,fruit mass / ° brix ratio. The data were submitted to analysis of variance by the F testand the Tukey test. Sources of compost based on organic compost and cattle manurefavored the vegetative and productive growth of the fig tree. Organic fertilization influencedpositively the development of the fig tree ’Roxo de valinhos’, being the compoundorganic and bovine manure the most suitable for the production of this species.